Potential of red guava fruitghurt in lowering blood glucose levels in streptozotocin induced rats - Ania K P Dewi; Rona J H Dewi; Endry Septiadi (ACTA Medical Health Sciences, 2022)
Diabetes mellitus is a chronic metabolic disorder characterized by increased blood glucose levels due to decreased insulin production, insulin action or both. Red guava fruitghurt contains flavonoid phytochemical compound. This research aims to determine the effect of red guava fruitghurt on reducing blood glucose levels in rats. The study was laboratory experiment. The subjects of this study were white rats (Rattus norvegicus) with wistar lines, where each group needed 5 rats, therefore the total was 25 rats. The sampling technique used is simple random sampling, The experimental animals are grouped into 5 groups, negative control, positive control, treatment 1 (administration of fruitghurt), treatment 2 (administration of glibenclamide), and treatment 3 (combination of fruitghurt and glibenclamide). The data analysis was performed with paired t test, one way anova, pairwise comparison test and post hoc duncan. The study found that red guava fruitghurt can reduce blood glucose levels in rats induced by streptozotocin and show a probability value or p value of 0.000 (p value < 0.05), meaning that there is a significant difference between Treatment 1, 2, and 3. The blood glucose level of rats after administration of fruitghurt was 75.4mg/dl, after administration of glibenclamide was 48.4mg/dl and the combination of fruitghurt and glibenclamide was 44.0mg/dl. From these data, it can be seen that the most influential treatment in reducing blood glucose levels is the combination of fruitghurt and glibenclamide. The significant effect in lowering blood glucose levels is the combination of fruitghurt and glibenclamide. DOI : 10.35990/amhs.v1n1.p19-27 REFERENCES Khairani, R. (2016). Prevalensi diabetes mellitus dan hubungannya dengan kualitas hidup lanjut usia di masyarakat. Universa Med, 26(1). Newman, W. A., & Kamus Saku Kedokteran Dorland. (2011). Kamus Saku Kedokteran Dorland (Ed. 28, Vol. 28). Djojoningrat, D. (2014). Buku Ajar Ilmu Penyakit Dalam (Edisi VI, Jilid I). Amir, S. M. J., Wungouw, H., & Pangemanan, D. (2015). Kadar glukosa darah sewaktu pada pasien diabetes melitus tipe 2 di Puskesmas Bahu Kota Manado. J e-Biomedik, 3(1). https://doi.org/10.35790/ebm.3.1.2015.6505 (2013). Global Status Report. NCD Executive Summary. New Dir Youth Dev, 2013(140). Kementerian Kesehatan Republik Indonesia. (2016). Mari Kita Cegah Diabetik Dengan Cerdik. (April 2015). Putra, J. S., Achmad, A., & Pramestutie, R. H. (2017). Kejadian efek samping potensial terapi obat anti diabetes pada pasien diabetes melitus berdasarkan algoritme Naranjo. Pharm J Indones, 2(2). https://doi.org/10.21776/ub.pji.2017.002.02.38 Rachmaniar, R., & Kartamihardja, H. (2016). Pemanfaatan sari buah jambu biji merah (Psidium guajava) sebagai antioksidan dalam bentuk granul effervescent. Indones J Pharm Sci Technol, 5(1). Labiba, N. M., Marjan, A. Q., & Nasrullah, N. (2020). Pengembangan soyghurt (yoghurt susu kacang kedelai) sebagai minuman probiotik tinggi isoflavon. Amerta Nutr, 4(3). https://doi.org/10.20473/amnt.v4i3.2020.244-249 Salimah, D. M., Lindriati, T., & Purnomo, B. H. (2015). Sifat fisik dan kimia puree jambu biji merah (Psidium guajava) dengan penambahan gum arab dan gum xanthan. J Agroteknologi, 09(02). Dewi, I. P., Septriani, R., Verawaty, V., & Mulyani, D. (2019). Daya antihiperglikemia yoghurt pada mencit putih jantan. J Katalisator, 4(2). https://doi.org/10.22216/jk.v4i2.4607 Shinta, A., & Kusuma, W. (2015). The effect of ethanol extract of soursop leaves (Annona muricata) to decreased levels of malondialdehyde. Vol 4. Nugraheni, A. A., Jaelani, M., Rahayuni, A., & Semedi, P. (2019). Efektifitas pemberian jus tomat dan jambu biji merah terhadap penurunan kolesterol total pada wanita overweight. J Ris GIZI, 7(2). https://doi.org/10.31983/jrg.v7i2.5121 Watanabe, D., Kuranuki, S., Sunto, A., Matsumoto, N., & Nakamura, T. (2018). Daily yogurt consumption improves glucose metabolism and insulin sensitivity in young nondiabetic Japanese subjects with type-2 diabetes risk alleles. Nutrients, 10(12). https://doi.org/10.3390/nu10121834 Arnanda, Q. P., & Nuwarda, R. F. (2019). Penggunaan radiofarmaka teknisium-99M dari senyawa glutation dan senyawa flavonoid sebagai deteksi dini radikal bebas pemicu kanker. Farmaka Suplemen, 14(1). Rezaei, M., Sanagoo, A., Jouybari, L., Behnampoo, N., & Kavosi, A. (2017). The effect of probiotic yogurt on blood glucose and cardiovascular biomarkers in patients with type II diabetes: A randomized controlled trial. Evid Based Care J, 6(4). https://doi.org/10.22038/ebcj.2016.7984 Wallace, B. Y. T. C., Velasco, A., Lay, T., et al. (2016). Pengaruh perbandingan jambu biji (Psidium guajava) dengan rosella (Hibiscus sabdariffa Linn) dan jenis jambu biji terhadap karakteristik jus. Bull Seismol Soc Am, 106(1). Novrial, D., Sulistyo, H., & Setiawati. (2013). Comparison of antidiabetic effects of honey, glibenclamide, metformin and their combination in the streptozotocin-induced diabetics rat. Semin Nas Kesehat Jur Kesehat Masy FKIK UNSOED. Lenzen, S. (2008). The mechanisms of alloxan- and streptozotocin-induced diabetes. Diabetologia, 51(2). https://doi.org/10.1007/s00125-007-0886-7 Saputra, N. T., Suartha, I. N., & Dharmayudha, A. A. G. O. (2018). Agen diabetagonik streptozotocin untuk membuat tikus putih jantan diabetes mellitus. Bul Vet Udayana. https://doi.org/10.24843/bulvet.2018.v10.i02.p02 Gomes, A. C., Bueno, A. A., De Souza, R. G. M. H., & Mota, J. F. (2014). Gut microbiota, probiotics and diabetes. Nutr J, 13(1). https://doi.org/10.1186/1475-2891-13-60 Sari, P. M. D. R. (2014). Studi literatur interaksi obat pada peresepan pasien diabetes melitus tipe 2 di instalasi rawat jalan RSUD Panembahan Senopati Bantul Yogyakarta periode Desember 2013. Fakultas Farmasi, Universitas Sanata Dharma Yogyakarta. König, A., Schwarzinger, B., Stadlbauer, V., et al. (2019). Guava (Psidium guajava) fruit extract prepared by supercritical CO₂ extraction inhibits intestinal glucose resorption in a double-blind, randomized clinical study. Nutrients, 11(7). https://doi.org/10.3390/nu11071512 Nilamaya, F. A. (2018). Pengaruh variasi konsentrasi perisa sari jambu biji merah (Psidium guajava) terhadap tingkat kesukaan panelis dan kandungan vitamin C pada yoghurt susu UHT (Ultra High Temperature). [Skripsi]. Rifdiyani, F. A. (2018). Pengaruh pemberian bakteri asam laktat Dangke jenis Lactobacillus plantarum dan Enterococcus faecium terhadap kadar glukosa darah mencit (Mus musculus) ICR jantan. [Skripsi].